Regional Economic Policy: Structural Approach and Tools (Theoretical Formulation) - Sukharev, Oleg Sergeevich (Economy of Regions, 2015)
The subject matter of the article - the development of the doctrine of “coherent” Regional Development and research of the structural quality of the development of regional systems on the basis of theoretical analysis of institutional factors (parameters) that determine the manufacturability of the regional economy. The purpose of the research - to show the possibilities of technological change and shift of economic growth in a particular regional system, with stringent limits for accelerated development, with an emphasis on industrial regions. To this end, formed a number of structural models and analyze the impact of technological factors on the growth parameters of the regional economy, the definition of conditions for the development of the industrial region. Methodology. The correlation and regression analysis are applied, which allows to establish a statistically significant relationship between the relevant parameters, the econometric models are used to demonstrate the possibility of estimating the growth parameters via the control parameters, including the technological factor. The structural aspect of regional economic growth is taken into account by the division of investment on the old and new technologies. Result and scope of the research. Increasing adaptability of the regional economy is possible at the expense of compounding results in the use of (old) and the application of new technologies. This principle specifies the algorithm of formation of regional development priorities, provides a choice of strategy of technological development of the regional system. Investing resources only in the field of new technologies can dramatically enhance the disparity of regional economic system, the parameters of diversion of resources and the creation of a new resource will determine the pace of growth in the region. Conclusions. Dynamics of investment into old technology provides a major impact on the rate of economic growth in the regions of Russia, despite the fact that investments in new technologies are small in size and did not have an equivalent impact on the economic growth rate in comparison with the old technology. Institutional correction parameters defining the diversion of resources from old technologies and the creation of a new resource development will determine the quality of the new economic growth.